Синтез атоматизованої системи багатоцільового управління хлібопекарським виробництвом - Шаруда, С. С. (Eastern-European Journal of Enterprise Technologies, 2009)
In this work bread making processes complexity is revealed. The usage of decision support system for technological processes management is shown to be useful. A structure of automation system for multipurpose management of technological processes is shown